Daya Terima Konsumen Dan Kandungan Gizi Tempe Kacang Tunggak Rumput Laut - Nurlaela Ramdani; Reni Sofiyatin; Lalu Khairul Abdi (Poltekkes Kemenkes Mataram, 2017)
Background. Tempe is a very popular food product in Indonesia which is processed with soy fermentation process in a certain time using Rhizopus sp. Shell that grows on soybeans will hydrolyze complex compounds into simple compounds that are easily digested by humans. In general, tempe has white characteristics due to the growth of mycelia-mycelia fungus that connects between soybean seeds to form a compact texture. The occurrence of degradation of soybean components during the fermentation that caused the emergence of a typical the cowpea producers seaweed flavor (Vigna unguiculata) is one type of nuts are well known and growing in Indonesia. The superiority of cowpea is easy to cultivate, contains high enough protein and the price is relatively affordable compared to soybeans. To verify the food, other mineral-rich foods can be added: Seaweed. This study aims to determine the capacity of grass beans in seaweed in Perumnas Market. Research Purposes. This research uses experimental method with laboratory experiment, Completely Random Design (RAL) one factorial that is addition of seaweed. Research Methods. Samples in this research is consumer panelist as much as 42 people. The data collected in the form of the identity data of the sample which includes age, sex, fondness to tempe cowpea seaweed. Of 42 consumer panelists there were 28 (67%) liked respondents and 14 (33%) respondents rather like marketing cow seaweed cowpea. Consumer panelist respondents were 23 persons (55%) and kos-kossan children (19%) (45%) .The organoleptic test data was analyzed using Analysis Of Variance (One Way Anova). At a 95% confidence level or α 0.05. Research Result. The results show that in terms of taste, texture, odor and color of treatment t1 is most favored by somewhat trained panelists. Conclusion that exists For color parameters, odors, flavors and textures have a value of p <0.05. This shows that the ratio of cowpea and seaweed has a significant influence on the color, smell, taste and texture of The cowpea producers seaweed.